UML MODELING OF WEBSITE-BASED BERLIANA LAUNDRY SYSTEM - Ana, Berli (Universitas Lampung, 2025)
Berliana Laundry, a newly launched website-based platform, emerges at a pivotal time coinciding with the significant growth in the laundry industry. This growth has propelled a high demand for laundry services that are fast, efficient, and of high quality. Prioritizing excellence in service and demonstrating a strong commitment to continuously enhancing service quality, Berliana Laundry aims to gain customer trust by prioritizing quality, efficiency, and convenience in its laundry services. The